The Impact of Intellectual Capital, Capital Structure, and Free Cash Flow on Firm Value - Dewi, Ni Kadek Risma Sintya Kadek Risma Sintya; Erawati, Ni Made Adi (E-Jurnal Akuntansi, 2024)
This study seeks to provide empirical evidence on the influence of intellectual capital, capital structure, and free cash flow on firm value, using company size as a control variable. The research focuses on companies in the property and real estate sector listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. A purposive sampling method was employed, yielding a sample of 66 companies with a total of 198 observations. Data analysis was conducted through multiple linear regression, utilizing SPSS software. The results indicate that intellectual capital exerts a positive and significant effect on firm value, suggesting that firms that effectively manage their intellectual resources enhance their market value. In contrast, capital structure shows no significant relationship with firm value, implying that variations in debt-to-equity ratios do not substantially influence the market valuation of companies in this sector. Furthermore, free cash flow was found to have a negative and significant impact on firm value, which may reflect agency problems where excess cash leads to inefficient investments that detract from shareholder value.